A Clinical Analysis of the Treatment of Chronic Coronary Artery Occlusion With Antegrade Dissection Reentry - Wu, Xiangjun; Zhang, Dan; Liu, Haitao; Li, Shuai; Fu, Chao; Liu, Jiyuan; Cui, Jiayu (Frontiers in Surgery, 2021)
Objective: This study aimed to investigate the efficacy and safety of antegrade dissection re-entry (ADR) technique in the percutaneous coronary intervention (PCI) to open chronic total occlusion (CTO) lesions. Methods: The baseline, angiographic results, PCI success rate, and major adverse cardiac events (MACE) during the 12 months of follow-up were compared between 48 patients who did not use ADR in the treatment of CTO lesions (control group) and 50 patients who used ADR (treatment group). Results: The control group comprised 48 patients who had 52 CTO lesions, and the treatment group comprised 50 patients who had 58 CTO lesions. The success rate of PCI in the treatment group (89.7% vs. 71.2%, P = 0.047) was significantly higher than in the control group, where six patients had in-stent restenosis (ISR, ISR-CTO) that were all recanalized. The mean PCI time (71 ± 25 min vs. 95 ± 33 min, P = 0.041), X-ray exposure time (42 ± 17 min vs. 71 ± 22 min, P = 0.032), contrast agent dosage (98 ± 26 ml vs. 178 ± 63 ml, P = 0.029), MACE incidence during the 12 months of follow-up (22.0% vs. 41.7%, P = 0.046) and recurrent myocardial infarction incidence (10.0% vs. 27.1%, P = 0.047) were significantly lower in the treatment group than in the control group. The differences were all statistically significant. Conclusion: It is safe and effective to use the ADR technique in PCI for coronary artery CTO lesions. The technique shortens the operation time, reduces the radiation dose of doctors and patients and the use dose of contrast agents, and improves patients’ prognoses.